Desenvolvimento de novos complexos de rutênio como potenciais agentes no tratamento de doenças cardiovasculares - Gouveia Júnior, Florêncio Sousa (2023)
In recent decades, ruthenium(II) complexes have been the subject of intense research for presenting great pharmacological potential for the treatment of several pathologies, among them cardiovascular diseases. Additionally, coordination compounds containing imidazole derivatives and NOx-type ligands have also shown to be promising systems due to their versatility and broad spectrum of therapeutic applications (anticancer, bactericidal, antihypertensive, for example). Therefore, this work aims to synthesize new complexes of the general formula cis-[RuII(phen)2L1L2]n+, where phen=1,10-phenanthroline, L1=2-methylimidazole (2MIM) or ethylenothiourea (ETU), L2=Cl⁻, NO+ or [N(O)SO3]⁻. The characterization was performed using spectroscopic techniques (vibrational spectroscopy in the infrared range, electronic spectroscopy and X ray absorption spectroscopy), mass spectrometry, 1H nuclear magnetic resonance, X ray diffraction and cyclic voltammetry, supporting the proposed structures. The nitrosyl complexes and compounds containing nitrosyl-sulfite were then studied for their ability to release nitric oxide (NO0) under different conditions. The spectroscopic monitoring during irradiation with blue light (λmax = 460 nm) showed controlled release of NO0, proportional to the time of exposure to light. The complexes have also been shown to be able to donate nitric oxide when reduced by l-glutathione. In this condition, there was also evidence of nitroxyl (HNO) release by the nitrosyl complexes, sustained by assays using the probes myoglobin and cPTIO. Spectrophotometric titration showed that the compounds cis-[Ru(NO)(phen)2(2MIM)]3+ and cis-[Ru(NO)(phen)2(ETU)]3+ have a pH of nitrosyl/nitro conversion equal to 5.66 and 6.53, respectively. The radical scavenger capabilities were evaluated and it was demonstrated both nitrosyl and nitrosyl-sulfite complexes can work as antioxidant compounds. Molecular docking simulations were executed in order to evaluate the possibility of interaction between the complexes and DNA or transport proteins (human serum albumin and apo-transferrin). The results suggest the existence of weak and moderate interactions, indicating low tendencies to cytotoxicity and to stable bonding with proteins. Experiments for partition coefficient determination (logP) suggested that all complexes are slightly hydrophilic. The anti-cancer activity of the complexes was tested against three tumor cell lines and it was found that the compounds have little toxicity, in addition to a modest selectivity for breast tumor cells. Vascular reactivity assays evidenced that all complexes can promote vasodilation, where the compound cis-[Ru(NO)(phen)2(2MIM)]3+ presented the best results, with EC50 values around 214 nmol L-1. On the next moment, the capability of the complexes containing the thioamide ligand ETU work as a hydrogen sulfide (H2S) donor was evaluated. Experiments with a H2S selective electrode evidenced the formation of sulfide in solution when the complexes react with thiols. That result was corroborated with the resazurin probe reduction experiment followed by fluorescent emission spectroscopy. Mass spectroscopy analyses suggested the formation of persulfides during the reduction with l-glutathione. Finally, the vasodilation activity of those complexes was evaluated in the presence of a H2S scavenger, where a partial suppression of the vascular relaxing could be observed. That evidenced the participation of H2S in the vasorelaxant activity of those compounds.